The Role Of Learning Agility And Work Engagement In Encouraging Innovative Work Behavior Among Millennial Employees - David Panjaitan; Vina Pebianti (Jurnal Fokus Manajemen, 2026)
Dynamic changes in the work environment require organizations to enhance innovative work behavior among employees, particularly among the millennial generation, which dominates the current workforce. This study aims to analyze the influence of learning agility and work engagement on innovative work behavior among millennial employees. The study used a quantitative approach with a survey method involving 150 millennial employees working in various industrial sectors in the Jakarta area. Quota sampling was used as the sampling technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of Smart PLS software. The results show that learning agility has a positive and significant effect on innovative work behavior. Furthermore, work engagement also has a positive and significant effect on innovative work behavior. These findings indicate that adaptive learning abilities and a high level of work engagement play a crucial role in fostering innovative work behavior among millennial employees. This research is expected to provide theoretical contributions to the development of human resource management literature and practical implications for organizations in designing employee management strategies oriented towards fostering innovation.